Ensaio clínico controlado aleatorizado do tratamento da halitose com terapia fotodinâmica em pacientes bronquiectásicos - Pinto, Erika Horácio (2016)
The association between oral health and chronic obstructive pulmonary disease (COPD) has been widely studied and the aspiration of microorganisms is one of the most accepted mechanisms for pulmonary exacerbation. Bronchiectasis has many clinical similarities with COPD, such increased morbidity and decreased quality of life. However, the oral health of these patients has not yet been studied to date. Since halitosis has been reported in these patients and the decrease in oral microbial load may contribute to the reduction of these exacerbations, the objective of this study was to evaluate the clinical effect of PDT in the treatment of halitosis in bronchiectasis patients, to assess oral health conditions and quality of life in this population. The study was divided into two phases: (1) 163 bronchiectasis and 163 healthy patients matched by gender, age and socioeconomic status were recruited. The clinical and periodontal examination and its classification were done through the Third National Health and Nutrition Examination Survey. Two quality of life instruments were applied: OHIP-14 and Saint George's Respiratory Questionnaire (SGRQ). In phase (2), the clinical effect of PDT was evaluated in both groups diagnosed with halitosis by gas chromatography in three phases (a) baseline, (b) after PDT (c) after periodontal treatment. The prevalence and severity of periodontal disease were higher in the BQT group (p <0.05) and all patients who had exacerbated in the last 3 months had periodontal disease. Out of the bronchiectasis patients, 50% report that the disease generates negative impacts on their quality of life. Therefore, it is concluded that PDT was effective in the treatment of halitosis in bronchiectasis patients. Bronchiectasis patients have poor oral health status and high prevalence of periodontal disease.